Patterns of Community Forests in Tropical Forest Conservation Action Program-Sumatera (TFCA-Sumatera) in Bengkulu POLA HUTAN RAKYAT PADA PROGRAM TROPICAL FOREST CONSERVATION ACTION (TFCA-SUMATERA) DI BENGKULU - Mike Dwi Hisma; Hardjanto .; Yulius Hero (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
The United States Government and the Indonesian Government have agreed on a treaty to reduce deforestation called the TFCA Sumatra Program (Tropical Forest Conservation Action-Sumatera). Development of community forests is expected to reduce the rate of deforestation. However, the pattern of effective community forest management to be applied in reducing the rate of deforestation in Sumatera was unknown, especially in the TFCA program in Bengkulu. The study was conducted in Air Sulau Village and Kayu Ajaran Village, South Bengkulu Regency. The respondents selection was conducted by purposive sampling. This study aimed to analyze the pattern of community forest management in the TFCA Sumatera in Bengkulu. The data was collected using observations, interviews, and literature study. The analysis was performed using descriptive-qualitative and quantitative methods. The results showed that the pattern of development community forests in the TFCA program in Bengkulu was agroforestry with predominantly agricultural crops such as rubber. Meanwhile, woody plants such as albizia have just been developed on community forest enterprises in Bengkulu, combined with seasonal crops such as cassava and maize, or with herbs like turmeric and ginger. Based on the fund sources, the community forest pattern in TFCA Sumatera in Bengkulu belongs to the community forest pattern with full subsidy.Keywords: Community forests, TFCA-Sumatera, agroforestry, development patterns